Thomas Jefferson, a biographical companion - Brown, David S. (David Scott) 1966- (Santa Barbara, Calif. ABC-CLIO, 1998)
An encyclopedia covering the life of Thomas Jefferson and the key issues, events, and personalities that shaped him.
Includes bibliographical references (p. 249-255) and index.
Keywords: Jefferson, Thomas -- 1743-1826 -- Encyclopedias, Juvenile; Jefferson, Thomas -- 1743-1826 -- Encyclopedias; Presidents -- United States -- Biography -- Encyclopedias, Juvenile; Presidents -- Encyclopedias